Inhibition of vesicular stomatitis virus infection by nitric oxide. - Bi, Z (1995)
Inhibitory effects of nitric oxide (NO) on vesicular stomatitis virus (VSV) infection were investigated by using a VSV-susceptible mouse neuroblastoma cell line, NB41A3. Productive VSV infection of NB41A3 cells was significantly inhibited by an organic NO donor, S-nitro-N-acetylpenicillamine (SNAP), while the control compound N-acetylpenicillamine (NAP) had no effect. Survival rate of VSV-infected cells was greatly increased by the treatment with SNAP, while the NAP treatment did not have any effect. Adding SNAP 30 min prior to infection resulted in complete inhibition of viral production when a low multiplicity of infection (MOI) was used. Substantial inhibition of viral production was also obtained with treating cells 6 h earlier before infection with a higher MOI. Activating the neuronal NO synthase by treating cells with N-methyl-D-aspartate (NMDA) led to significant inhibition of viral production by cells infected at the three doses of virus tested (MOIs of 0.1, 1, and 5). The inhibitory effect of NMDA on viral infection was totally blocked by the NO synthase inhibitor N-methyl-L-arginine. However, adding hemoglobin, a strong NO-binding protein and thus an inactivator of NO activity, did not reverse the NMDA-induced inhibition of viral production, suggesting that NO might exert its antiviral effects inside the NO-producing cells. Collectively, these data support the anti-VSV effects of NO, which might be one of the important factors of natural immunity in controlling the initial stages of VSV infection in the central nervous system.